Pengelolaan Zakāt Māl oleh UPZ Kecamatan Bukit Kemuning: Analisis Manajerial dan Tantangan Implementatif dalam Perspektif Islam - Lasinem Lasinem; Finny Ligery; Muhamad Agus Mushodiq (Bulletin of Indonesian Islamic Studies, 2024)
This study aims to analyze the management of zakāt māl by the Zakat Collection Unit (UPZ) of Bukit Kemuning Subdistrict, North Lampung Regency, from the perspective of Islamic management. The research focuses on four key managerial functions: planning, organizing, implementation, and supervision. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings indicate that the UPZ has implemented a structured zakat management system, including the preparation of an Annual Work and Budget Plan (RKAT), the establishment of operational divisions, and the implementation of both consumptive and productive distribution programs. However, several challenges remain, such as low public literacy regarding zakat, limited human resources, and low participation of zakat payers (muzakkī) through official institutions. The zakat utilization strategy is directed toward the economic empowerment of beneficiaries (mustaḥiq) through micro-enterprise capital assistance and business mentoring. Supervision is conducted in multiple layers by BAZNAS, the Inspectorate, and the Ministry of Religious Affairs to ensure accountability and compliance with Islamic law. This study recommends strengthening zakat education, enhancing institutional capacity, and optimizing productive programs to realize effective, transparent, and impactful zakat management for the long-term welfare of the ummah.